2005
DOI: 10.1074/jbc.m414260200
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-dependent Aminoacyl-adenylate Hydrolysis by a Nonediting Class I Aminoacyl-tRNA Synthetase

Abstract: Glutaminyl-tRNA synthetase generates Gln-tRNA Gln 10 7 -fold more efficiently than Glu-tRNA Gln and requires tRNA to synthesize the activated aminoacyl adenylate in the first step of the reaction. To examine the role of tRNA in amino acid activation more closely, several assays employing a tRNA analog in which the 2-OH group at the 3-terminal A76 nucleotide is replaced with hydrogen (tRNA 2H Gln ) were developed. These experiments revealed a 10 4 -fold reduction in k cat /K m in the presence of the analog, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(126 citation statements)
references
References 52 publications
3
122
1
Order By: Relevance
“…By constructing parallel reactions where one series employs labeled [ 14 C]-amino acid, and a second set that employs [α-32 P] ATP, one can experimentally measure the ratio of ATP consumption to production of AAtRNA AA formed ( Figure 5B). Such experiments have provided insight into the role that tRNA plays in the kinetics of adenylation reaction [66], and into mechanisms for pre-transfer editing [55].…”
Section: Rapid Quench Methods For Studying the Half Reactions Of Aminmentioning
confidence: 99%
See 1 more Smart Citation
“…By constructing parallel reactions where one series employs labeled [ 14 C]-amino acid, and a second set that employs [α-32 P] ATP, one can experimentally measure the ratio of ATP consumption to production of AAtRNA AA formed ( Figure 5B). Such experiments have provided insight into the role that tRNA plays in the kinetics of adenylation reaction [66], and into mechanisms for pre-transfer editing [55].…”
Section: Rapid Quench Methods For Studying the Half Reactions Of Aminmentioning
confidence: 99%
“…The pyrophosphate exchange assay described above technically measures the rate of isotopic exchange of 32 P into ATP, and can provide information about the kinetic mechanism (i.e., whether substrate binding is random or ordered) [54]. As described in Section 2.9, the forward reaction alone may be measured directly by use of [α-32 P]-labeled ATP, monitoring conversion of ATP to AMP using thin-layer chromatography [55]. The advantage of this approach is that it enables separate detection of AMP and aminoacyl~AMP on the TLC plates.…”
Section: Pyrophosphate Exchange Assaymentioning
confidence: 99%
“…A fluorescent-based translocation assay in IleRS has shown that ATP evacuates the aminoacylation active site during editing (14,17,34,35), but the molecular details of translocation remain unclear. Alternatively, a recent investigation with glutaminyl (Gln)-tRNA synthetase proposed that some tRNA synthetases may hydrolyze aminoacyl-adenylate intermediates directly within the synthetic active site (8).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently hypothesized that a pretransfer editing activity might be conferred in the synthetic active site (8). Under pyrophosphate exchange conditions (see Fig.…”
Section: Rescue Of a Pretransfer Editing Activity In Leursmentioning
confidence: 99%
See 1 more Smart Citation